2022
DOI: 10.1038/s41598-022-19362-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in 50 kHz call subtypes emitted during tickling-induced playful behaviour in rats

Abstract: Abstract‘Tickling’ induces positive affective states in laboratory rats as evidenced by the production of 50-kHz ultrasonic vocalisations (USVs), although this has mostly been investigated in males. Juvenile rats emit distinctive 50-kHz USV subtypes. Frequency-modulated (FM) 50-kHz USVs are thought to be associated with positive affect and flat 50-kHz USVs with social communication. FM and flat USVs are produced by both sexes during tickling, but it is unclear whether these calls are produced in relation to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…We also found small but statistically significant differences in the spectral characteristics of the recorded vocalizations across the various social contexts. Overall, these results add to multiple recent studies demonstrating that rat USVs are age-sex- and social status-dependent, and hence may convey social information during social interactions 4145 .…”
Section: Discussionsupporting
confidence: 74%
“…We also found small but statistically significant differences in the spectral characteristics of the recorded vocalizations across the various social contexts. Overall, these results add to multiple recent studies demonstrating that rat USVs are age-sex- and social status-dependent, and hence may convey social information during social interactions 4145 .…”
Section: Discussionsupporting
confidence: 74%
“…Our previous study showed that one subtype of 50 kHz USVs ( at) were paired with scampering behaviours in females more than males, while frequency-modulated subtype calls were paired with scampering behaviours in both tickled males and females. This suggests that there is a temporal link between tickle-induced vocalisations and solitary play behaviours [ 20 ].…”
Section: Discussionmentioning
confidence: 97%
“…In this study we investigated whether the hypothalamic oxytocin and vasopressin systems are active during a playful tickling stimulus by quantifying Fos-ir in oxytocin and vasopressin neurons via immunohistochemical double labelling. As we have previously provided evidence of sex differences in tickle-induced behaviours [ 20 ], we also compared double labelling between male and female juvenile Wistar rats. Tickling elicited more 50 kHz USVs and scampering behaviours than controls, with females expressing higher levels of both behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results add to multiple recent studies demonstrating that rat USVs are age, sex, and social status dependent and hence may convey social information during social interactions. 41 , 42 , 43 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%